Réponses

  • Omnes
  • Modérateur confirmé
2014-03-03T00:05:00+01:00
Salut,

A = 7x² -9x
A = x(7x-9)

C = - 3x (x + 2) - (x+2)(2x-3)
C = (x+2)[-3x - (2x-3)]
C = (x+2)(-3x-2x+3)
C = (x+2)(-5x+3)

D = 1 - (x + 1)²
D = 1² - (x+1)²
D = (1 - (x+1))(1+(x+1))
D = (1-x-1)(1+x+1)
D = -x(x+2)

E = (x + 3)² - (4x - 6)²

E = [(x+3)-(4x-6)][(x+3)+(4x-6)]
E = (x+3-4x+6)(x+3+4x-6)
E = (-3x+9)(5x-3)
E = 3(-x+3)(5x-3

Bonne soirée !

2014-03-03T00:28:24+01:00


A = 7x² - 9x

A = x ( 7x - 9)
C = - 3x (x + 2) - (x+2)(2x-3)

C = (x+2) (- 3x - 2x +3)

C = (x+2) ( -5x +3)

D = 1 - (x + 1)²

D = 1-( x² + 2x + 1)

D = 1 - x² - 2x - 1

D = -x ( x+2)

E = (x + 3)² - (4x - 6)²

E = (x+3 - 4x + 6) ( x+3 + 4x - 6)

E = (- 3 x + 9) (5x - 3 )

E = 3 (-x +3) ( 5x -3)